2013
DOI: 10.1002/ps.3548
|View full text |Cite
|
Sign up to set email alerts
|

Nematotoxicity of drupacine and a Cephalotaxus alkaloid preparation against the plant‐parasitic nematodes Meloidogyne incognita and Bursaphelenchus xylophilus

Abstract: BACKGROUND: Species of Cephalotaxus (the plum yews) produce nematotoxic compounds of unknown identity. Consequently, bioassay-guided fractionation was employed to identify the compound(s) in Cephalotaxus fortunei twigs and leaves with activity against plant-parasitic nematodes.RESULTS: A crude alkaloid extract, particularly drupacine, was responsible for much of the nematotoxicity. The ED 50 of drupacine for Bursaphelenchus xylophilus was 27.1 µg mL −1 , and for Meloidogyne incognita it was 76.3 µg mL −1 . Imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 35 publications
2
15
0
1
Order By: Relevance
“…Lupin seed alkaloids could hence contribute to the development of novel compounds able to break resistance as observed inhibitory effects were shared across trichostrongylid species. This finding is in line with previous works in helminths of veterinary or medical importance 31-34 or plant-parasitic nematodes 35,36 that also evidenced the anthelmintic potential of plant extracted alkaloids. Our results also suggested that lupin extracts would control multidrug-resistant field isolate, which is an important consideration given the threat to sustainable control impeded by such isolates worldwide, including Europe 37 .…”
Section: Discussionsupporting
confidence: 92%
“…Lupin seed alkaloids could hence contribute to the development of novel compounds able to break resistance as observed inhibitory effects were shared across trichostrongylid species. This finding is in line with previous works in helminths of veterinary or medical importance 31-34 or plant-parasitic nematodes 35,36 that also evidenced the anthelmintic potential of plant extracted alkaloids. Our results also suggested that lupin extracts would control multidrug-resistant field isolate, which is an important consideration given the threat to sustainable control impeded by such isolates worldwide, including Europe 37 .…”
Section: Discussionsupporting
confidence: 92%
“…The biofumigation experiments indicated that VOC may act alone or synergistically with non-VOC to reduce the viability of M. incognita, which also has been observed by other authors working on diverse green residues (Bailey and Lazarovits 2003;Estupiñan-López et al 2017;Lord et al 2011;Neves et al 2007;Ploeg 2008;Ploeg and Stapleton 2001;Roubtsova et al 2007;Wen et al 2013). Biofumigation is traditionally performed with Brassica spp., which produce VOC and non-VOC with toxic effect against plant-parasitic nematodes (Aissani et al 2015;Al-Rehiayani et al 1999;Neves et al 2007;Ngala et al 2015;Roubtsova et al 2007).…”
Section: Discussionsupporting
confidence: 70%
“…However, these six compounds have only weak nematicidal activity against B. xylophilus . The nematotoxicity of drupacine and a Cephalotaxus alkaloid preparation against B. xylophilus and the root‐parasitic nematode Meloidogyne incognita has recently been reported . Although the nematicidal activities of numerous phytochemicals, including essential oils and alkaloids, against B. xylophilus have been described, the nematicidal activities of flavonoids and coumarins from S. chamaejasme roots against B. xylophilus and B. mucronatus are reported for the first time in the present study.…”
Section: Resultsmentioning
confidence: 62%